Energy efficiency on the product roadmap: An empirical study across releases of a software product. Issue 2 (7th February 2017) - Jagroep, Erik; Procaccianti, Giuseppe; van der Werf, Jan Martijn; Brinkkemper, Sjaak; Blom, Leen; van Vliet, Rob
Abstract: In the quest for energy efficient Information and Communication Technology, research has mostly focused on the role of hardware. However, the impact of software on energy consumption has been acknowledged as significant by researchers in software engineering. In spite of that, due to cost and time constraints, many software producing organizations are unable to effectively measure software energy consumption preventing them to include energy efficiency in the product roadmap. In this paper, we apply a software energy profiling method to reliably compare the energy consumed by a commercial software product across 2 consecutive releases. We demonstrate how the method can be applied and provide an in‐depth analysis of energy consumption of software components. Additionally, we investigate the added value of these measurement for multiple stakeholders in a software producing organization, by means of semistructured interviews. Our results show how the introduction of an encryption module caused a noticeable increase in the energy consumption of the product. Such results were deemed valuable by the stakeholders and provided insights on how specific software changes might affect energy consumption. In addition, our interviews show that such a quantification of software energy consumption helps to create awareness and eventually consider energy efficiency aspects when planning software releases. Abstract : We introduce a software energy profiling method to reliably compare the energy consumed by a commercial software product across two consecutive releases. In an experiment, we showed how specific software changes affected energy consumption and the added value of the measurements when planning software releases. Ultimately, we extend the control software product organizations have over their software products.